Thermal process for jerky provides proper lethality for controlling pathogens - Roberts, M.N.; Getty, Kelly J. K.; Boyle, Elizabeth A. E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In 2003, the New Mexico Department of Health linked an outbreak of Salmonellosis with consumption of beef jerky. Due to the increasing commonality of foodborne illness associated with dried meats, in 2004 USDA/FSIS published the Compliance Guideline for Meat and Poultry Jerky Produced by Small and Very Small Plants, which addresses the issues of how to obtain adequate lethality and verify adequate drying. Small meat businesses that produce jerky products must validate that their processes achieve a 5-log reduction of E. coli O157:H7 and a > 6.5-log reduction of Salmonella. The objective of this study was to determine the effects of thermal processing temperatures and times on reducing E. coli O157:H7 and Salmonella in chopped and formed beef jerky.
Keywords: Beef; Cattle; Lethality; Jerky